Detection of neuron-derived pathological α-synuclein in blood - Kluge, Annika; Bunk, Josina; Schaeffer, Eva; Drobny, Alice; Xiang, Wei; Knacke, Henrike; Bub, Simon; Lückstädt, Wiebke; Arnold, Philipp; Lucius, Ralph; Berg, Daniela; Zunke, Friederike (Brain (London, England : 1878), 2022)
To date, no reliable clinically applicable biomarker has been established for Parkinson's disease. Our results indicate that a long anticipated blood test for Parkinson's disease may be realized. Following the isolation of neuron-derived extracellular vesicles of Parkinson's disease patients and non-Parkinson's disease individuals, immunoblot analyses were performed to detect extracellular vesicle-derived α-synuclein. Pathological α-synuclein forms derived from neuronal extracellular vesicles could be detected under native conditions and were significantly increased in all individuals with Parkinson's disease and clearly distinguished disease from the non-disease state. By performing an α-synuclein seeding assay these soluble conformers could be amplified and seeding of pathological protein folding was demonstrated. Amplified α-synuclein conformers exhibited β-sheet-rich structures and a fibrillary appearance. Our study demonstrates that the detection of pathological α-synuclein conformers from neuron-derived extracellular vesicles from blood plasma samples has the potential to evolve into a blood-biomarker of Parkinson's disease that is still lacking so far. Moreover, the distribution of seeding-competent α-synuclein within blood exosomes sheds a new light of pathological disease mechanisms in neurodegenerative disorders.